2019
DOI: 10.5004/dwt.2019.24148
|View full text |Cite
|
Sign up to set email alerts
|

Detection and removing of lead from wastewater using chemical treatment of polyurethane foam waste: Batch and column experiments

Abstract: A new inexpensive sorbent was prepared from the waste of polyurethane foam (PUF) which highly surface polarity and sorption capacity. PUF was modified by adding amino, chloro and hydroxyl groups to its matrix. The polyamine polyhydroxy polyurethane chloride (PPPC) was characterized by using elemental analysis (EA), bulk conductivity (BC,σ), infrared/ultraviolet/visible spectra (IR/UV/Vis), pH point zero charge (pH ZCP), thermal analysis (TGA/DTA/DSC), scanning electron microscope (SEM) and X-ray diffraction (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The PUFWs spectrum showed that the absorption peaks were appeared at 369, 337, 336, 218, and 209 nm due to π-π * transition localized on the conjugated system. The spectrum of PUF-COO@MnO 2 shows short peaks from 372 to 376 nm and higher band at 353-369 nm that may attributed to n-π * transition which indicate successful addition of MnO 2 into the PUFWs matrix (Moawed et al 2019).…”
Section: Characterization Of Puf-coo@mno 2 Nanocompositementioning
confidence: 95%
“…The PUFWs spectrum showed that the absorption peaks were appeared at 369, 337, 336, 218, and 209 nm due to π-π * transition localized on the conjugated system. The spectrum of PUF-COO@MnO 2 shows short peaks from 372 to 376 nm and higher band at 353-369 nm that may attributed to n-π * transition which indicate successful addition of MnO 2 into the PUFWs matrix (Moawed et al 2019).…”
Section: Characterization Of Puf-coo@mno 2 Nanocompositementioning
confidence: 95%
“…Water is the key to life, and it is very necessary for agriculture and in the activity of every day for living organisms (Schmidt et al 2020;Kenawy et al 2022). The biggest problem is that it is not always found in sufficient quantity and the required quality (Moawed et al 2019;Torres-Badajoz et al 2022). Nevertheless, the increased use of water in modern industries makes it vulnerable to pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethane foam (PUF) has gained interest for use as a sorbent for lead [ 20 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Many previous works have been devoted to pretreatment for the determination of lead by atomic absorption spectrometry.…”
Section: Introductionmentioning
confidence: 99%